2019
DOI: 10.1371/journal.pone.0217414
|View full text |Cite
|
Sign up to set email alerts
|

Linking human behaviours and malaria vector biting risk in south-eastern Tanzania

Abstract: To accelerate malaria elimination in areas where core interventions such as insecticide-treated nets (ITNs) are already widely used, it is crucial to consider additional factors associated with persistent transmission. Qualitative data on human behaviours and perceptions regarding malaria risk was triangulated with quantitative data on Anopheles mosquito bites occurring indoors and outdoors in south-eastern Tanzania communities where ITNS are already used but lower level malaria transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
170
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(181 citation statements)
references
References 41 publications
11
170
0
Order By: Relevance
“…It was also noted that policy makers, regulators and scientists pointed to statistical evidence of declining malaria prevalence, as reported in recent Tanzania's malaria indicator surveys [3,57], while community members pointed mostly to the lived experiences of witnessing fewer episodes of malaria and reduced severity of the disease. All participants commended the country's efforts in providing universal coverage with LLINs, reliable diagnosis and affordable treatment, whose effectiveness has been demonstrated in various studies [7,58,59]. There was also a general but not unanimous agreement that current interventions will not be sufficient to achieve further reductions of the malaria burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also noted that policy makers, regulators and scientists pointed to statistical evidence of declining malaria prevalence, as reported in recent Tanzania's malaria indicator surveys [3,57], while community members pointed mostly to the lived experiences of witnessing fewer episodes of malaria and reduced severity of the disease. All participants commended the country's efforts in providing universal coverage with LLINs, reliable diagnosis and affordable treatment, whose effectiveness has been demonstrated in various studies [7,58,59]. There was also a general but not unanimous agreement that current interventions will not be sufficient to achieve further reductions of the malaria burden.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a general but not unanimous agreement that current interventions will not be sufficient to achieve further reductions of the malaria burden. Participants listed various challenges, such as insecticide resistance and outdoor biting exposure, which have been registered in many field studies [5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, assessment of interaction between resting surfaces and time of collection suggested that the time of collection had little to no effect on resting preference of mosquitoes (Additional file 1). Indoor residual spraying (IRS) and long-lasting insecticide-treated nets (LLINs), despite having been tremendously impactful [2], are now perceived as inadequate for the goal of malaria elimination [59][60][61], partly due to the rise of insecticide resistance [10,11] and changes in mosquito biting behaviours [12][13][14]. These challenges may result from, and can be compounded by extensive and improper implementation of the insecticide based strategies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to previous efforts, these efforts are primarily reliant on ITNs [now long-lasting insecticide-treated nets (LLINs)], IRS and effective case management [1]. Despite proven effectiveness of the vector control interventions, LLINs and IRS are negatively affected by insecticide resistance [10,11], increasing outdoor-biting [12][13][14], high costs and the sub-optimal coverage and usage at community and household level. Resistance is often associated with exposure of vectors to insecticides used in agriculture [15] and public health [16,17], and the indoor interventions may also induce shifts in vector biting and resting behaviours [18][19][20].…”
mentioning
confidence: 99%